GRP Receptor Regulates Depression Behavior via Interaction With 5-HT2a Receptor - Xiang, Dan; Wang, Huiling; Sun, Siqi; Yao, Lihua; Li, Ruiting; Zong, Xiaofen; Wang, Gaohua; Liu, Zhongchun (Frontiers in Psychiatry, 2020)
Objective Accumulating evidences indicate that gastrin-releasing peptide receptor (GRPR) may contribute to the pathophysiology of depression. However, the mechanism of the involvement of GRPR in the progression of depression remains unclear. Here, we showed the extent to which stress and antidepressant treatment impact GRPR expression, and explored the interactions between 5-HT2a receptor (5-HT2aR) and GRPR at the cellular level. Methods The rat depression models were created with chronic unpredictable mild stress (CUMS). Then, these rats were treated with ﬂuoxetine for 4 weeks after CUMS. We measured body weight and performed behavioral tests to determine the effects of stress and fluoxetine on depressive-like behaviors. Real-time PCR and western blotting were used to measure the mRNA and protein expression levels of GRPR in the hypothalamus. Then, Flag-tagged protein (pcmv-Flag-5HT2aR) and Myc-tagged protein (pcmv-Myc-GRPR) expression vectors were constructed, identified, and transfected into human embryo kidney 293 (HEK293) cells. The interaction between 5-HT2aR and GRPR was detected by coimmunoprecipitation and double-label immunofluorescence. Results The rats subjected to 4 weeks of CUMS showed depressive-like behaviors, including decreased body weight, sucrose preference, and distance traveled, rearing frequency and velocity in the open field test and increased immobility time in the forced swimming test. Fluoxetine treatment reversed CUMS-induced depressive-like behavior. The mRNA and protein expression of GRPR in the hypothalamus was significantly increased after 4 weeks CUMS exposure, and treatment with fluoxetine reversed these changes. Coimmunoprecipitation showed that 5-HT2aR and GRPR combine with each other in vitro. Immunofluorescence revealed that the 5-HT2aR and GRPR were colocalization in both the cell membrane and cytoplasm. Conclusion Our study enhances the understanding of the involvement of GRPR in depression. This study also provides in vitro experimental evidence of the interaction between 5-HT2aR and GRPR, which may play an important role in the pathogenesis of depression.